The birth of computer vision - Dobson, James E. (Book collections on Project MUSE., 2023)
"Today's most advanced neural networks and sophisticated image-analysis methods come from 1950s and '60s Cold War culture-and many biases and ways of understanding the world from that era persist along with them. The Birth of Computer Vision uncovers these histories and finds connections between the algorithms, people, and politics at the core of automating perception today"--